A proposed algorithm for initiation of renal replacement therapy in adult critically ill patients - Bagshaw, Sean M (BioMed Central, 2009)
Critically ill patients whose course is complicated by acute kidney injury often receive renal replacement therapy (RRT). For these patients, initiation of RRT results in a considerable escalation in both the complexity and associated cost of care. While RRT is extensively used in clinical practice, there remains uncertainty about the ideal circumstances of when to initiate RRT and for what indications. The process of deciding when to initiate RRT in critically ill patients is complex and is influenced by numerous factors, including patient-specific and clinician-specific factors and those related to local organizational/logistical issues. Studies have shown marked variation between clinicians, and across institutions and countries. As a consequence, analysis of ideal circumstances under which to initiate RRT is challenging. Recognizing this limitation, we review the available data and propose a clinical algorithm to aid in the decision for RRT initiation in critically ill adult patients. The algorithm incorporates several patient-specific factors, based on evidence when available, that may decisively influence when to initiate RRT. The objective of this algorithm is to provide a starting point to guide clinicians on when to initiate RRT in critically ill adult patients. In addition, the proposed algorithm is intended to provide a foundation for prospective evaluation and the development of a broad consensus on when to initiate RRT in critically ill patients.